Correction to: Glycosylation of dentin matrix protein 1 is a novel key element for astrocyte maturation and BBB integrity - Bo Jing; Chunxue Zhang; Xianjun Liu; Liqiang Zhou; Jiping Liu; Yinan Yao; Juehua Yu; Yuteng Weng; Min Pan; Jie Liu; Zuolin Wang; Yao Sun; et al. (Protein & Cell, 2018)
In the original publication, the label of Fig. 2C should be read as “GFAP/lectin/DAPI” not “DMP1/GFAP/lectin/DAPI”.